Implementation of Religious Activities at SMPN 2 Cikarang Utara to Increase Student Learning Motivation in PAI Subjects - Nisa Aulia Luthfiyanto; Opik Taufikurahman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research was motivated by the decline in students' learning motivation which occurred due to the transition period of the Covid-19 pandemic which was still felt by female students, resulting in students still being carried away by the online atmosphere and their motivation to study decreased. Apart from that, this research is intended to describe the implementation of students' religious activities at SMPN 2 Cikarang Utara to increase students' learning motivation, especially in PAI subjects. The method in this research is a qualitative descriptive research method with a case study approach. Data was obtained through direct interviews and field observations as well as documentation analysis. The research results from this research are: SMPN 2 Cikarang Utara has habituation activities that can increase students' learning motivation, including; (1) 3 S activities (Smile Greetings), (2) SABAR (Breakfast Together) activities, (3) Literacy Activities, (4) Congregational Dhuha Prayer Activities. Apart from that, there are also religious activities, one of which is PHBI activities which consist of; (1) Prophet's birthday activities, (2) Isra' Mi'raj activities (3) Ramadhan Islamic boarding school activities.